O tempo de cada um: turismo e estratégias familiares em uma comunidade de pescadores no Parque Nacional dos Lençóis Maranhenses - SANTOS, Lícia Cristina Viana Silva (2021)
The present work focuses on the analysis of family strategies of some families from Atins, aimed at reconciling activities traditionally carried out with those related to tourism. The empirical universe of the research is Atins, a village that has part of its territorial base within the limits of the Lençóis Maranhenses National Park, created in 1981, which has become one of the main tourist destinations in the country. The work seeks to discuss the functioning of the social life of families in this location in two moments - the low and high season of tourism. Based on the functioning of social life in those moments, and with seasonality as a central element, the discussions held seek to understand the way time is managed by families, and the family strategies used to carry out different activities related to tourism. The arrangements involving the members of the family units, in addition to functioning as alternatives for generating income, are interpreted in the work as strategies and forms of resistance, since they are inserted in an integral protection conservation unit that, according to the legislation in force, does not admits the presence of families. In addition to these limitations, they are also threatened by initiatives by political and economic agents aimed at tourism on a business basis that do not take into account local initiatives. Based on the notion of strategy, this work pays attention, on the one hand, to family arrangements aimed at different activities and, on the other, to collective actions engendered as a way of responding to threats caused by political and economic agents who are interested in establishing businesses in the region where Atins and other traditional communities are located. Faced with this threat scenario, the mobilization of families is motivated by the defense of their way of life and the permanence in their territory.